Preliminary evidence that brief exposure to vaccination-related internet memes may influence intentions to vaccinate against COVID-19. (June 2022) - Geniole, Shawn N.; Bird, Brian M.; Witzel, Alayna; McEvoy, Jordan T.; Proietti, Valentina
Abstract: Despite global efforts to rapidly distribute COVID-19 vaccines, early estimates suggested that 29–35% of the population were hesitant/unwilling to receive them. Countering such vaccine hesitancy is thus an important priority. Across two sets of online studies (total n = 1584) conducted in the UK before (August–October 2020) and immediately after the first effective vaccine was publicly announced (November 10–19, 2020), brief exposure (<1 min) to vaccination memes boosted the potentially life-saving intention to vaccinate against COVID-19. These intention-boosting effects, however, weakened once a COVID-19 vaccine became a reality (i.e., after the announcement of a safe/effective vaccine), suggesting meme-based persuasion may be context-dependent. These findings thus represent preliminary evidence that naturally circulating memes may—under certain circumstances—influence public intentions to vaccinate, although more research regarding this context-specificity, as well as the potential psychological mechanisms through which memes act, is needed. Highlights: Many report(ed) unwillingness or hesitancy to receive COVID-19 vaccinations. Vax-supportive or antivax-critical memes may influence this willingness. A sample of such memes were shown to participants. This meme exposure increased COVID-19 vaccination intentions. These effects weakened after a safe/effective vaccine was announced.